Small nucleolar RNA signatures of lung tumor-initiating cells - Mannoor, Kaiissar (BioMed Central, 2014)
BACKGROUND: Non-small cell lung cancer (NSCLC) is the number one cancer killer. Tumor-initiating cells (TICs) are responsible for tumor progression and recurrence. Emerging evidences suggest that small nucleolar RNAs (snoRNAs) play malfunctioning roles in lung tumorigenesis. This study aims to determine if snoRNAs have important function in lung TICs by: 1) profiling and comparing snoRNA expression patterns in lung ALDH1+/- cells of 28 primary NSCLC tissues to identify new signatures of TICs; 2) determining prognostic significance of the snoRNA signatures by analyzing the expression in 82 NSCLC tissues with different stages and histological types using quantitative PCR; 3) functionally investigating if the snoRNAs contribute to stemness of lung TICs using in vitro and in vivo assays. RESULTS: Twenty-two snoRNAs were identified whose changes were specific to the TICs. The expression of two snoRNAs (snoRA3 and snoRA42) was inversely associated with survival of NSCLC patients (P = 0.002, p = 0.001, respectively). Functional analysis indicated that snoRA42 was upregulated in CD133+ cells isolated from NSCLC cell lines compared with the CD133- counterparts. snoRA42 knockdown reduced the proliferation and self-renewal of TICs in vitro. However, ectopic expression of snoRA42 in non-TICs enhanced the potentials of cell proliferation and self-renewal. snoRA42 expression was associated with expression of stem cell-core transcription factors in lung TICs. Blocking snoRA42 expression in TIC xenografts decreased tumorigenesis in mice. CONCLUSIONS: The snoRNA signatures of lung TICs provide potential biomarkers for predicting outcome of NSCLC. snoRA42 is one of the important snoRNAs in regulating features of lung TICs, and thus contributes to lung tumorigenesis.